Numerical elastoplastic analysis of the shear stress distribution in the adhesive layer for single-lap joints - Pekbey Yeliz (Science and Engineering of Composite Materials, 2014)
The purpose of this paper was to investigate the stress distribution of adhesive single-lap joint loaded in the elastic and elastoplastic range. The stress variation across the adhesive length was achieved both analytically and numerically. A two-dimensional finite element solution presented a detailed picture of the stress behavior in a single-lap joint loaded in the elastic and elastoplastic range. After the finite element results matched very well with results obtained from analytic solution in the elastic range, it was decided that adhesive plasticity needed to be added to the finite element models in order to make them as accurate as possible. The residual stresses after elastic-plastic loading were calculated. The results obtained from numerical analysis showed that the residual stress was important as the joint strength can be increased by residual stresses. In addition, the effect of the adhesive length, thickness of adhesive, and thickness of adherends on the shear distribution of the adhesive was examined numerically by using elastoplastic finite element method. The target was to change the geometry of the joint and study its effects on the stress distribution in the adhesive.